Mapping Plankton Community Structure in North Sulawesi Waters Using Ecological Diversity Indices as Indicators of Marine Ecosystem Health - Rose O.S.E. Mantiri; Deiske A. Sumilat; Suzanne L. Undap; Rowen Bonaventura; Haryati Rabuka; Tesalonika S. Koloay (Postgraduate, University of Mataram, 2026)
Plankton communities play a crucial role in marine ecosystems and are widely used as bioindicators of environmental quality. This study aimed to map plankton community structure in several coastal waters of North Sulawesi and evaluate their potential as indicators of marine ecosystem health. Plankton samples were collected from Bunaken, Lembeh Strait, Amurang, Belang, and Likupang using standard plankton net tows. Community structure was analyzed using species composition, abundance, Shannon–Wiener diversity index (H′), evenness (E), and dominance (D). The results showed clear spatial variation in plankton community structure among study sites. Higher diversity values were recorded in Bunaken (H′ = 2.78; E = 0.81; D = 0.18) and Lembeh Strait (H′ = 2.65; E = 0.79; D = 0.21), indicating relatively stable marine conditions. In contrast, Likupang exhibited lower diversity and higher dominance (H′ = 1.43; E = 0.52; D = 0.39), suggesting greater environmental stress. These patterns demonstrate that plankton community indices are sensitive indicators of ecosystem condition in tropical coastal waters. The findings also highlight the potential use of plankton ecological data as contextual learning resources in science education, particularly for teaching marine ecosystem dynamics, biodiversity, and environmental monitoring using real environmental datasets from local coastal ecosystems